DISCUSSING SUDDEN UNEXPECTED DEATH IN EPILEPSY: ARE WE EMPOWERING OUR PATIENTS?. Issue 11 (14th October 2015) - Keddie, Stephen; Angus-Leppan, Heather; Parker, Thomas; Toescu, Sebastian; Nash, Adina; Adewunmi, Lola; Liu, Rebecca
Abstract : Disparity exists between clinical practice and guidelines on discussion of Sudden death in epilepsy (SUDEP) with patients. This study examined how patients were informed about SUDEP; the impact of such discussion, and their views on the discussion. Methods: A quantitative/qualitative questionnaire was given to 50 consenting patients attending epilepsy clinics. Exclusions were patients with intellectual disability, and/or those deemed at risk of negative consequences on completing the study. Results: 98% of patients were aware of the importance of medication adherence, 78% of driving regulations in epilepsy, and 84% of factors influencing seizure frequency. Only 50% of patients were aware of SUDEP and 38% of status epilepticus. 42% of patients preferred SUDEP information at diagnosis and 36% only after three clinic appointments. Negative emotional responses (in 38%), and not behavioural changes, resulted from SUDEP discussions. Conclusions: In this small in-depth study, only half the patients recalled information about SUDEP. More than one-third of patients reported adverse consequences. There was no improvement in self-management. We suggest a paradigm shift: embedding SUDEP discussion with all potential complications of epilepsy; and emphasising optimal healthcare and self-management. This model has been successfully applied in other areas to empower patients and improve outcome.